Characterizing the Vocal Fold Epithelial Response to Recovery following Phonation‐Induced Trauma at the Transcriptional Level. (2nd September 2014) - Valenzuela, Carla V.; Kojima, Tsuyoshi; Greene, Scott M.; Dharamsi, Latif M.; Novaleski, Carolyn K.; Garrett, C. Gaelyn; Rousseau, Bernard
Abstract : Objectives: It is unknown how acute episodes of phonotrauma affect the recovery of the vocal fold epithelial barrier. The epithelial barrier is characterized by specialized adhesive structures. Our objective was to evaluate the gene expression of junctional complex proteins and inflammatory mediators following phonation‐induced trauma in an in vivo rabbit model. Methods: Sixty‐five New Zealand white breeder rabbits were randomized to normal (n = 5), modal intensity (n = 30), or raised intensity (n = 30) phonation for 120 minutes. Larynges were harvested at 0 hours, 4 hours, 8 hours, 1 day, 3 days, or 7 days following phonation and compared with normal. Real‐time polymerase chain reaction was used to evaluate mRNA expression of occludin, zonula occluden‐1 (ZO‐1), E‐cadherin, β‐catenin, interleukin 1β (IL‐1β), cyclooxygenase‐2 (COX‐2), and transforming growth factor β‐1 (TGFβ1). Results: Both phonation groups demonstrated a down‐regulation of occludin between 8 hours and 1 day ( P <. 016), and ZO‐1 levels at 3 days ( P =. 08). β‐catenin and E‐cadherin demonstrated an inverse relationship at 8 hours in the modal phonation group ( P =. 08). IL‐1β, COX‐2, and TGFβ1 levels peaked at 8 hours in the modal intensity group ( P =. 08), with TGFβ1 peaking at day 1 in the raised intensity group ( P =. 08). Conclusions: Results revealed a critical time point at 8 hours and 1 day in which most junctional complex and inflammatory markers decreased or peaked. Given the mechanical stresses that the vocal folds must withstand on a regular basis, time‐dependent changes in barrier and inflammatory gene regulation are critical to understanding vocal fold homeostasis and tissue recovery.